Relationship between hydrogen embrittlement and Md30 temperature: Prediction of low-nickel austenitic stainless steel's resistance. (20th September 2019) - Izawa, Chika; Wagner, Stefan; Deutges, Martin; Martín, Mauro; Weber, Sebastian; Pargeter, Richard; Michler, Thorsten; Uchida, Haru-Hisa; Gemma, Ryota; Pundt, Astrid
Abstract: Hydrogen embrittlement (HE) of several low-nickel austenitic stainless steels (AISI 300 series) was studied with special attention to the impact of strain induced α′-martensite. The susceptibility of the steels to HE is judged with respect to the relative reduction of area (RRA): The HE susceptibility is lower for larger RRA-values. Strain-induced martensite formation was evaluated within in the framework of the Olson-Cohen model, revealing a linear relationship between RRA and the probability β of martensite nucleus formation in the steels. In order to widen the scope of data evaluation to literature data, the consideration of a parameter alternative to β is required. It is demonstrated that among other parameters the Md30 temperature (Nohara), which assesses the stability against martensitic transformation, can serve as an indicator to predict HE of AISI 300 series steels. Regarding the Md30 temperature (Nohara), a trend-line with respect to the RRA-values is found. Thereby, the RRA-values of low-nickel austenitic stainless steels group into three distinct regimes; (1) for Md30  > −80 °C, where RRA-values decrease with increasing Md30 temperature, (2) at Md30  ≈ −80 °C, where RRA-values show a large variation ('threshold band'), and (3) for Md30  < −80 °C, showing constant RRA-values of nearly 100%. Some RRA data points that deviate from the trend line can be explained by the special microstructure of the investigated samples. Graphical abstract: Image 1 Highlights: Hydrogen embrittlement of AISI 300 series steels was studied via RRA values. Probability of strain induced martensite formation scales with RRA. Md30 temperature (Nohara) yields a trend line with RRA. Three distinct Md30 regimes are established with RRA, enabling the steel's classification. Steels deviating from the trend line possess a special surface oxide.